Effects of sedentary behaviour interventions on biomarkers of cardiometabolic risk in adults: systematic review with meta-analyses. Issue 3 (8th April 2020) - Hadgraft, Nyssa T; Winkler, Elisabeth; Climie, Rachel E; Grace, Megan S; Romero, Lorena; Owen, Neville; Dunstan, David; Healy, Genevieve; Dempsey, Paddy C
Abstract : Context/purpose: Observational and acute laboratory intervention research has shown that excessive sedentary time is associated adversely with cardiometabolic biomarkers. This systematic review with meta-analyses synthesises results from free living interventions targeting reductions in sedentary behaviour alone or combined with increases in physical activity. Methods: Six electronic databases were searched up to August 2019 for sedentary behaviour interventions in adults lasting for ≥7 days publishing cardiometabolic biomarker outcomes covering body anthropometry, blood pressure, glucose and lipid metabolism, and inflammation (54 studies). The pooled effectiveness of intervention net of control on 15 biomarker outcomes was evaluated using random effects meta-analyses in the studies with control groups not providing other relevant interventions (33 studies; 6–25 interventions analysed). Results: Interventions between 2 weeks and <6 months in non-clinical populations from North America, Europe and Australia comprised much of the evidence base. Pooled effects revealed small, significant (p<0.05) beneficial effects on weight (≈ −0.6 kg), waist circumference (≈ −0.7 cm), percentage body fat (≈ −0.3 %), systolic blood pressure (≈ −1.1 mm Hg), insulin (≈ −1.4 pM) and high-density lipoprotein cholesterol (≈ 0.04 mM). Pooled effects on the other biomarkers (p>0.05) were also small, and beneficial in direction except for fat-free mass (≈ 0.0 kg). Heterogeneity ranged widely (I 2 =0.0–72.9). Conclusions: Our review of interventions targeting sedentary behaviour reductions alone, or combined with increases in physical activity, found evidence of effectiveness for improving some cardiometabolic risk biomarkers to a small degree. There was insufficient evidence to evaluate inflammation or vascular function. Key limitations to the underlying evidence base include a paucity of high-quality studies, interventions lasting for ≥12 months, sensitive biomarkers and clinical study populations (eg, type 2 diabetes). PROSPERO trial registration number: CRD42016041742